Does Cup Position at the High Hip Center or Anatomic Hip Center in THA for Developmental Dysplasia of the Hip Result in Better Harris Hip Scores and Revision Incidence? A Systematic Review. Issue 5 (May 2021) - Stirling, Patrick; Viamont-Guerra, Maria-Roxana; Strom, Louise; Chen, Antonia F.; Saffarini, Mo; Nover, Luca; Laude, Frederic
Abstract: Background: One goal of THA is to restore the anatomic hip center, which can be achieved in hips with developmental dysplasia by placing cups at the level of the native acetabulum. However, this might require adjuvant procedures such as femoral shortening osteotomy. Another option is to place the cup at the high hip center, potentially reducing surgical complexity. Currently, no clear consensus exists regarding which of these cup positions might offer better functional outcomes or long-term survival. Question/purpose: We performed a systematic review to determine whether (1) functional outcomes as measured by the Harris hip score, (2) revision incidence, and (3) complications that do not result in revision differ based on the position of the acetabular cup (high hip center versus anatomic hip center) in patients undergoing THA for developmental dysplasia of the hip (DDH). Methods: We performed a systematic review using Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, including studies comparing the functional outcomes, revision incidence, and complications of primary THA in dysplastic hips with acetabular cups placed at the high hip center versus those placed at the anatomic hip center, over any time frame. The review protocol was registered with PROSPERO (registration number CRD42020168183) before commencement. Of 238 records, eight comparative, retrospective nonrandomized studies of interventions were eligible for our systematic review, reporting on 207 hips with cups placed at the high hip center and 268 hips with cups at the anatomic hip center. Risk of bias within eligible studies was assessed using the Risk Of Bias In Non-randomized Studies of Interventions tool. Due to low comparability between studies, data could not be pooled, so these studies were assessed without summary effects. Results: Six studies compared Harris hip scores, two of which favored high hip center cup placement and three of which favored anatomic hip center cup placement, although none of the differences between cohorts met the minimum clinically important difference. Five studies reliably compared revision incidence, which ranged from 2% to 9% for high hip center at 7 to 15 years and 0% to 5.9% for anatomic hip center at 6 to 16 years. Five studies reported intra- and postoperative complications, with the high hip center being associated with higher incidence of dislocation and lower incidence of neurological complications. No clear difference was observed in intraoperative complications between the high hip center and anatomic hip center. Conclusion: No obvious differences could be observed in Harris hip score or revision incidence after THA for osteoarthritis secondary to DDH between cups placed at the anatomic hip center and those placed at the high hip center. Placement of the acetabular cup in the high hip center may lead to higher risk of dislocation but lower risk of neurologic complications, although no difference in intraoperative complications was observed. Surgeons should be able to achieve satisfactory functional scores and revision incidence using either technique, although they should be aware of how their choice influences hip biomechanics and the need for adjunct procedures and associated risks and operative time. These recommendations should be considered with respect to the several limitations in the studies reviewed, including the presence of serious confounding factors and selection biases, inconsistent definitions of the high hip center, variations in dysplasia severity, small sample sizes, and follow-up periods. These weaknesses should be addressed in well-designed future studies. Level of Evidence: Level III, therapeutic study.